Perirhinal accumulation of neuronal alpha‐synuclein in a multiple system atrophy patient with dementia. Issue 5 (16th April 2017) - Saito, Mari; Hara, Makoto; Ebashi, Momoko; Morita, Akihiko; Okada, Kyoko; Homma, Taku; Sugitani, Masahiko; Endo, Kentaro; Uchihara, Toshiki; Kamei, Satoshi
Abstract : We report the case of a 79‐year‐old Japanese woman who developed cerebellar ataxia followed by rigidity, dysautonomia and cognitive disorders, and was thus clinically diagnosed as having possible MSA with dementia. Neuropathological findings demonstrated not only olivopontocerebellar and striatonigral degeneration with frequent glial cytoplasmic inclusions (GCIs), but also degenerative changes in the parahippocampal region, accentuated in the anterior portion of perirhinal cortex, where neuronal cytoplasmic inclusions (NCIs) and NFTs were numerous while GCIs were limited. NCIs were frequent in the deep layer, whereas NFTs were more frequent in superficial cortical layers. Other hippocampal subregions including subiculum, dentate fascia and cornu ammonis were minimally involved. NCIs in the perirhinal cortex showed intense argyrophilia with the Campbell‐Switzer silver impregnation method, but not argyrophilic with the Gallyas method. Most neuronal alpha‐synuclein aggregates in dendrosomatic fraction formed globular/tadpole‐like, and ultrastructurally comprised granular‐coated fine fibrils 12–24 nm in diameter. To the best of our knowledge, alpha‐synuclein‐related neuronal pathology localized in the perirhinal region without hippocampal involvement has not been previously reported in MSA, and may provide clues to elucidate how neuronal pathology evolves in the hippocampal/parahippocampal regions in MSA, particularly in cases with dementia.